STATISTICAL ANALYSIS OF FOREIGN TRADE OF UKRAINE - Голубова, Г. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
In the article the statistical analysis of Ukraine's foreign trade for 2008-2012 bienniums, and analyzed its foreign trade turnover, calculated number of statistical indicators characterizing the status and conditions for the development of Ukraine's foreign trade.